On Islam - Kuyper, Abraham, 1837-1920.; Bratt, James D., 1949-; Howard, Douglas A. (Douglas Arthur), 1958-; Vliet, Jan van; Harinck, George, 1958-; Obenchain, Diane Burdette (Ashland : Lexham Press, 2018)
Annotation At the beginning of the twentieth century, famed theologian Abraham Kuyper toured the Mediterranean world and encountered Islam for the first time. Part travelogue, part cultural critique, On Islam presents a European imperialist seeing firsthand the damage colonialism had caused and the value of a religion he had never truly understood. Here, Kuyper's doctrine of common grace shines as he displays a nuanced and respectful understanding of the Muslim world. Though an ardent Calvinist, Kuyper still knew that God's grace is expressed to unbelievers. Kuyper saw Islam as a culture and religion with much to offer the West, but also as a threat to the gospel of Jesus Christ. Here he expresses a balanced view of early twentieth-century Islam that demands attention from the majority world today as well. Essays by prominent scholars bookend the volume, showing the relevance of these teachings in our time.
Chapter 10: ConclusionSemitic, Aryan, and the Mediterranean as the Crossroads of Civilization; Afterword: By What Magic Did Muhammad â#x80;Œ?: The Missiological Implications of Abraham Kuyperâ#x80;#x99;s Observations on Islam; An Uneasy Admiration of Islam; Viewing Islam in Kuyperâ#x80;#x99;s Theological Context; Godâ#x80;#x99;s Covenantal Relationship with Humanity; The Covenant with Noah; The Covenant with Abraham; The Covenant with Moses; The Covenant with David; The New Covenant in Jesus Christ; What Muslims Know: Possible Answers to Kuyperâ#x80;#x99;s Question; Turning from â#x80;#x9C;Religionâ#x80;#x9D; to â#x80;#x9C;Relationshipâ#x80;#x9D;; Conclusion.
Print version record.
Includes bibliographical references.
eBooks on EBSCOhost
Keywords: Islam; Islam; Islam; RELIGION -- Islam -- General; Islam